Situational Leadership of the Head of Madrasah in Improving Teacher Discipline at Islamic Elementary Schools - Nurul Ulfa Ramadhani; Sarah Fadilah Azzahra; Gunawan; Mudasir (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Teacher discipline poses a persistent management challenge in Indonesian private Islamic primary schools, where structural constraints including financial uncertainty and geographical remoteness compound individual and institutional factors. This study investigates (1) the leadership style applied by the principal; (2) the factors inhibiting teacher discipline; and (3) the principal’s strategies for improving teacher discipline at Madrasah Ibtidaiyah (MI) Al-Fursan Pekanbaru. A qualitative phenomenological inquiry design was employed, drawing on the lived experiences of all 13 participants: the school principal (1) and all classroom teachers at MI Al-Fursan (12), selected through total population sampling given the school’s small size. Data were gathered through in-depth interviews, structured observation, and documentation analysis, and analysed through an adapted phenomenological procedure comprising epoché, horizonalization of significant statements, and thematic clustering, complemented by the interactive model of Miles, Huberman, and Saldaña (2014). Credibility was established through source and method triangulation and member checking. Findings reveal that the principal operates through situational leadership that contextually combines democratic engagement in collective policy-making with firm, rule-based authority enforcement in disciplinary matters. Inhibiting factors span three structural levels: geographical (long commuting distances), professional-individual (uneven awareness of professional obligation), and institutional-financial (delayed salary payments). The principal responds through four complementary strategies: motivational guidance, participatory deliberation, professional role modelling, and systematic performance monitoring. These findings contribute to understanding how principals in resource-constrained private Islamic schools exercise contextually adaptive leadership within conditions of structural vulnerability that exist beyond individual control.